2015
DOI: 10.1074/jbc.m115.655787
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis Stimulates Bone Resorption by Enhancing RANKL (Receptor Activator of NF-κB Ligand) through Activation of Toll-like Receptor 2 in Osteoblasts

Abstract: Background: Inflammation causes bone loss through enhanced osteoclast formation. Results: Porphyromonas gingivalis stimulates osteoclast formation through Toll-like receptor 2. Conclusion: Activation of Toll-like receptors may represent a mechanism for inflammation-induced bone loss in diseases like rheumatoid arthritis and periodontitis. Significance: A thorough understanding of the mechanisms involved in inflammation-induced bone loss will lead to improved treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 53 publications
3
88
0
3
Order By: Relevance
“…Here, we found a strong upregulation of TLR2 after osteogenic differentiation (Figure A–D), suggesting that TLR2 is crucially involved in osteoblast metabolism. Indeed, studies showed that osteoblasts produce the osteoclast‐stimulator RANKL in response to bacterial‐induced TLR2 activation . Additionally, C5aR1‐mediated effects in osteoblasts involve the induction of RANKL .…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found a strong upregulation of TLR2 after osteogenic differentiation (Figure A–D), suggesting that TLR2 is crucially involved in osteoblast metabolism. Indeed, studies showed that osteoblasts produce the osteoclast‐stimulator RANKL in response to bacterial‐induced TLR2 activation . Additionally, C5aR1‐mediated effects in osteoblasts involve the induction of RANKL .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, lipopolysaccharides (LPS) from Gram− bacteria, for example, P. gingivalis , can directly affect the bone remodelling via LPS binding to Toll‐like receptors (TLRs), which are expressed on osteoblasts, and thereby induce RANKL expression (Kassem et al. ). Subsequently, the reduction of Gram−/anaerobic bacteria caused by EMD in this study can possibly decrease bone resorption when TLRs are not activated.…”
Section: Discussionmentioning
confidence: 99%
“…Alveolar bone loss elicited by Porphyromonas gingivalis shares many features of lysis attending OM. Cytokine release (166) as well as induction of RANKL downstream of TLR2 and NOD2 are the prominent pathways leading to osteoclast activation in periodontitis (167,168). IL-17 is also markedly increased in periodontitis and appears to be an important factor in both inflammation and osteolysis of the periodontal tissue (169).…”
Section: Infection-associated Osteolysismentioning
confidence: 99%